Readiness of the Interns to work at rural area: a cross-sectional survey in a backward district of West Bengal - Samanta, Sumana; Maji, Baisakhi; Narayan, Ravi Kant (International Journal Of Community Medicine And Public Health, 2023)
Background: The scarcity of qualified doctors in rural areas remains a critical challenge for the health sector in India Aim was to analyze the perception of medical students regarding upcoming compulsory rural posting for 1 year as a part of their rotatory internship Methods: A cross-sectional survey was conducted in a medical college of West Bengal among the interns during March 2019 to February 2020. By doing complete enumeration of the interns present at the end of their Community Medicine posting, the sample size became 125. Predesigned, semi structured questionnaire was used for data collection. At the end of community medicine posting, when the interns came to department for completion, the printed questionnaire were given to them for filled up by their own. Collected data were entered in MS excel spreadsheet and analyzed with the help of SPSS 22.0 version. Results: About 74% interns thought it was difficult to serve the rural areas however 52% felt it will enrich their professional skills and about 65% thought it would be beneficial to the rural community. Only 22.4% were in favour of rural posting during their internship and 46% thought paying bond money is a good way out. Lengthening of MBBS course, inadequate clinical exposure, poor connectivity, no job satisfaction, obstructed career growth, no quality of life, insecure working environment for women, excessive workload, inadequate monetary compensation were the major reasons identified by interns for noncompliance of compulsory rural service during internship. Conclusions: The policymakers and medical educators need to design newer strategies for the improvement of rural healthcare facility keeping in mind the perception of students regarding rural service in the present scenario.